Safeguarding the welfare of refugee children in Ghana: Perspectives of practitioners in refugee camps - Abdullah, Alhassan; Mbamba, Crispin R.; Amponsah, Enoch B.; Frederico, Margarita; Cudjoe, Ebenezer; Bentum, Hajara; Emery, Clifton R. (Children and youth services review, 2023)
•Child sexual abuse is a major concern in refugee camps in Ghana.•Refugees in refugee camps establish strong connections with local residents in the community, but distance themselves from professionals within the refugee camps.•Effective collaboration between community leaders, professionals and refugees in refugee camp can be useful in addressing safeguarding concerns, including CSA, in refugee camps. Abuse and maltreatment within refugee camps remains a major concern. The situation is exacerbated in low-income countries due to the challenges associated with lack of available expert staff and limited financial resources necessary to safeguard the welfare of children. This study draws on the experiences of practitioners (including social workers, health workers and non-professional caregivers/volunteers) from refugee camps in Ghana, on measures to safeguard the welfare of refugee children. Semi-structured qualitative interviews were conducted with 13 practitioners from three refugee camps in Ghana. Narratives from the practitioners were organized using NVivo, and analyzed following strategies of initial and focused coding from the constructivist grounded theory approach. Child sexual abuse (CSA) was identified as the most common maltreatment across the refugee camps and continues to increase due to the increased lawlessness and lack of response from refugees. The following key safeguarding measures emerged from the practitioners’ narratives; community education; gendered-informed interventions; developing child inclusive practices, capability building of staff and tripartite collaborative approach between expert professionals, volunteers and senior community leaders. The findings suggest the need to increase the understanding of social workers and professionals in refugee camps on the cultural nuances among refugees and develop collaboration with community leaders to respond to the multicultural needs of refugees.